2022
DOI: 10.1007/s40272-022-00492-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute Tolerability of Methylphenidate in Treatment-Naïve Children with ADHD: An Analysis of Naturalistically Collected Data from Clinical Practice

Abstract: ObjectivesThe acute tolerability of methylphenidate (MPH) in children with attention-deficit/hyperactivity disorder (ADHD) has been studied mainly in research samples. Taking advantage of the mandatory test-dose procedure required for starting MPH in Italy, this study aimed to assess the incidence of intolerable adverse events after initial exposure to MPH in routine clinical practice. Methods The medical records of 480 consecutively treated, previously drug-naïve children and adolescents with ADHD (90% male, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Between studies differences may be accounted by differences in sample and methodology. Masi et al (52) have recently highlighted that intellectual disability increases the risk of any adverse event, especially irritability, suggesting that it may be linked to low tolerability to drug treatment. On the other hand, Nayak et al (42) showed that when controlling for the presence of side effects, the association between ADHD severity and poor adherence became nonsigni cant.…”
Section: Discussionmentioning
confidence: 99%
“…Between studies differences may be accounted by differences in sample and methodology. Masi et al (52) have recently highlighted that intellectual disability increases the risk of any adverse event, especially irritability, suggesting that it may be linked to low tolerability to drug treatment. On the other hand, Nayak et al (42) showed that when controlling for the presence of side effects, the association between ADHD severity and poor adherence became nonsigni cant.…”
Section: Discussionmentioning
confidence: 99%